Use of GPS communication on the railroad - Amochaeva, G.P.; Alpyssova, G.K.; Zhanasbaeva, А.S.; Rogovaya, X.S. (KSU Publ., 2017)
Introduction of the modern satellite technologies in optimization of management of infrastructure and traffic safety on the Karaganda railroad is a basis of transition to complex management information technologies of the highway work with use of means of satellite navigation, monitoring and communication. The main objective of creation of road geo-informational system is introduction of new technologies in the sphere of safety and train dispatching, management of transportation process and logistic operations, monitoring of infrastructure condition, engineering geodetic support of works on projection, construction and operation of the railroads. This article describes the GLONASS / GPS monitoring system. The main advantages of implementing this system in the work of railway transport are indicated. The principles of operation of the monitored monitoring system are presented in the form of illustrations and structural diagrams. The use of GLONASS / GPS monitoring system using ground-based correcting GPS stations will ensure fast and high-quality engineering and geodesic performance in the design, construction, repair and maintenance of Karaganda railway facilities.
Темір жолда GPS байланысын қолдану
Использование GPS связи на железной дороге
Keywords: traffic control center; wireless system; mobile solution; GPS monitoring; GIS map